Perceived needs of disability grant recipients in a semi-rural South African area - Frieg, A; Hendry, JA (Social Work/Maatskaplike Werk, 2001)
In South Africa many persons with disabilities and their families rely on social assistance from the government (Mbeki, 1997). According to the White Paper for Social Welfare (1997) 8, 7% of the 1995/96 consolidated national budget was allocated to the welfare budget, the largest proportion (88%) being utilised for social assistance. Of this, 24% was allocated to disability grants. Persons with disabilities often approach social workers in the public sector for assistance in their application for a disability grant. Persons with disabilities who are unable to work owing to their disabilities may apply for such a grant by submitting the relevant documentation as stipulated by the Social Assistance Act (Government Gazette No. 59 of 1992), the Welfare Amendments Act ( Govemment Gazette No. 106 of 1997) and the Regulation Gazette (Government Gazette No. R 417 of 1998). The grant is allocated on a sliding scale depending on the individual's income and assets.